2020
DOI: 10.1186/s12931-020-01509-7
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of adaptive servo-ventilation settings in a real-life multicenter study: pay attention to volume!

Abstract: Backgrounds To explain the excess cardiovascular mortality observed in the SERVE-HF study, it was hypothesized that the high-pressure ASV default settings used lead to inappropriate ventilation, cascading negative consequences (i.e. not only pro-arrythmogenic effects through metabolic/electrolyte abnormalities, but also lower cardiac output). The aims of this study are: i) to describe ASV-settings for long-term ASV-populations in real-life conditions; ii) to describe the associated minute-venti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 43 publications
1
2
0
1
Order By: Relevance
“…This is consistent with data from a German study, which reported that TE-CSA was the indication for ASV therapy in 67% of the 264 patients studied [49]. In contrast, 20% of patients enrolled in a prospective study of ASV in clinical practice had TE-CSA, whereas most ASV users (60%) had pre-existing CSA [48]. The official definition of TE-CSA states that cardiovascular disease should be ruled out as a cause for TE-CSA [30].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This is consistent with data from a German study, which reported that TE-CSA was the indication for ASV therapy in 67% of the 264 patients studied [49]. In contrast, 20% of patients enrolled in a prospective study of ASV in clinical practice had TE-CSA, whereas most ASV users (60%) had pre-existing CSA [48]. The official definition of TE-CSA states that cardiovascular disease should be ruled out as a cause for TE-CSA [30].…”
Section: Discussionsupporting
confidence: 89%
“…This difference compared with current guidelines is a limitation of the registry. However, most patients with TE-CSA also have cardiovascular comorbidities, as also documented in other registries [48][49][50]. Furthermore, the prevalence of TE-CSA or persisting CSA in patients with normal levels of B-type natriuretic peptide (BNP) has been shown to be low [51], while TE-CSA is common in patients with OSA and heart failure initially treated with CPAP [50].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Dieses Ergebnis fand sich auch in einer anderen Studie [18] . Diese hat von 177 Patienten mit Cheyne-Stokes-Atmung, die mit 2 verschiedenen ASV-Geräten behandelt wurden, viele Daten u. a. die Atemminutenvolumina aus den Geräten erfasst.…”
Section: Originalarbeitunclassified